MicroRNA-708 regulates CD38 expression through signaling pathways JNK MAP kinase and PTEN/AKT in human airway smooth muscle cells - Dileepan, Mythili (BioMed Central, 2014)
BACKGROUND: The cell-surface protein CD38 mediates airway smooth muscle (ASM) contractility by generating cyclic ADP-ribose, a calcium-mobilizing molecule. In human ASM cells, TNF-α augments CD38 expression transcriptionally by NF-κB and AP-1 activation and involving MAPK and PI3K signaling. CD38(−/−) mice develop attenuated airway hyperresponsiveness following allergen or cytokine challenge. The post-transcriptional regulation of CD38 expression in ASM is relatively less understood. In ASM, microRNAs (miRNAs) regulate inflammation, contractility, and hyperproliferation. The 3’ Untranslated Region (3’UTR) of CD38 has multiple miRNA binding sites, including a site for miR-708. MiR-708 is known to regulate PI3K/AKT signaling and hyperproliferation of other cell types. We investigated miR-708 expression, its regulation of CD38 expression and the underlying mechanisms involved in such regulation in human ASM cells. METHODS: Growth-arrested human ASM cells from asthmatic and non-asthmatic donors were used. MiRNA and mRNA expression were measured by quantitative real-time PCR. CD38 enzymatic activity was measured by a reverse cyclase assay. Total and phosphorylated MAPKs and PI3K/AKT as well as enzymes that regulate their activation were determined by Western blot analysis of cell lysates following miRNA transfection and TNF-α stimulation. Dual luciferase reporter assays were performed to determine whether miR-708 binds directly to CD38 3’UTR to alter gene expression. RESULTS: Using target prediction algorithms, we identified several miRNAs with potential CD38 3’UTR target sites and determined miR-708 as a potential candidate for regulation of CD38 expression based on its expression and regulation by TNF-α. TNF-α caused a decrease in miR-708 expression in cells from non-asthmatics while it increased its expression in cells from asthmatics. Dual luciferase reporter assays in NIH-3 T3 cells revealed regulation of expression by direct binding of miR-708 to CD38 3’UTR. In ASM cells, miR-708 decreased CD38 expression by decreasing phosphorylation of JNK MAPK and AKT. These effects were associated with increased expression of MKP-1, a MAP kinase phosphatase and PTEN, a phosphatase that terminates PI3 kinase signaling. CONCLUSIONS: In human ASM cells, TNF-α-induced CD38 expression is regulated by miR-708 directly binding to 3’UTR and indirectly by regulating JNK MAPK and PI3K/AKT signaling and has the potential to control airway inflammation, ASM contractility and proliferation.